Cycling or swap biologics and small molecules in psoriatic arthritis: Observations from a real-life single center cohort. Issue 16 (23rd April 2021) - Ariani, Alarico; Santilli, Daniele; Mozzani, Flavio; Lumetti, Federica; Lucchini, Gianluca; Di Donato, Eleonora; Giordano, Salvatore; Riva, Michele; Becciolini, Andrea
Abstract : Abstract: During the last years there has been an increasing availability of drugs (biologics and small molecules) with different mechanisms of action (MoA) in psoriatic arthritis (PsA). New issues about treatment strategies have arisen. The main aim of this study is to verify if there is a difference in terms of clinical efficacy (i.e. retention rate) between cycling (i.e. treating patients with the same MoA after the failure of the previous one) or swap (i.e choosing drugs with a MoA different from the failed previous one) strategies in PsA. In this mono-centric medical records review study, PsA patients treated with biologics, apremilast or tofacitinib were enrolled. Every prescription was clustered in three groups: cycling (CG), swap (SG) or first line group (1LG). Kaplan-Meier analysis and Cox test estimated and compared drugs' retention rate in CG, SG and 1LG. P  < .05 was considered statistically significant. One hundred eighty-three PsA patients were enrolled (9967 patient-months). In CG and 1LG the more prescribed drugs were tumor necrosis factor inhibitor (respectively 99% and 89%), in SG interleukin 17 inhibitor (60%). There were no differences in terms of sex, age, disease duration, and retention rate between CG and SG. The 18-months retention rate of 1LG, SG and CG was 77%, 60%, and 51% respectively. The CG retention rate was lower than in 1LG ( P  = .03). The findings of this study suggest that in PsA the swap strategy gives no remarkable advantage compared to cycling. However, patients undergoing swap strategy may experience the same failure rate observed in naives.